2006
DOI: 10.3928/1081-597x-20060501-15
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Keratitis Following Excimer Laser Application

Abstract: PURPOSE: To report two cases of herpes simplex keratitis following excimer laser application. METHODS:Two immunocompetent patients with no history of ocular viral infection developed ulcers after LASIK and phototherapeutic keratectomy (PTK), respectively. RESULTS: Antiviral treatment was administered, and the lesions healed within 14 days. CONCLUSIONS:These two cases suggest that herpes simplex virus was associated with the use of the excimer laser. [J Refract Surg. 2006;22:509-511.]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…43 This trend complements existing data suggesting a relationship between excimer laser procedures and HSV keratitis. 7 Post-LASIK HSV keratitis has been reported in patients with and without a history of herpetic disease. 7,44 None of the 5 HSV keratitis patients in our study presented with a known history of ocular or labial herpetic disease, reiterating that lack of known primary herpetic disease should not preclude a diagnosis of HSV keratitis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…43 This trend complements existing data suggesting a relationship between excimer laser procedures and HSV keratitis. 7 Post-LASIK HSV keratitis has been reported in patients with and without a history of herpetic disease. 7,44 None of the 5 HSV keratitis patients in our study presented with a known history of ocular or labial herpetic disease, reiterating that lack of known primary herpetic disease should not preclude a diagnosis of HSV keratitis.…”
Section: Discussionmentioning
confidence: 98%
“…7 Post-LASIK HSV keratitis has been reported in patients with and without a history of herpetic disease. 7,44 None of the 5 HSV keratitis patients in our study presented with a known history of ocular or labial herpetic disease, reiterating that lack of known primary herpetic disease should not preclude a diagnosis of HSV keratitis. 45 Although the literature reports good visual outcomes after resolution of HSV keratitis, all 5 of our patients with HSV keratitis developed some degree of visual loss as a result of scarring.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In animal models, reactivation of latent HSV after LASIK has been shown 1 ; however, only 6 cases have been reported after LASIK in humans. [2][3][4][5][6] Between 60% and 90% of the adult population is HSV-1-positive. 11 If we take into account that each year an estimated 48 000 cases 12 of active HSV eye disease present in the United States and hundreds of thousands of LASIK procedures are performed annually, a larger number of cases of recurrent HSV disease after LASIK could be expected to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Laser in situ keratomileusis has been shown to reactivate HSV-1 in rabbits, 1 and a few anecdotal reports [2][3][4][5][6] suggest that LASIK could trigger ocular HSV reactivation in humans. However, based on the same model 7 and 2 short series in humans, 8,9 it has been suggested that prophylactic perioperative antiviral therapy can protect the cornea from HSV reactivation after LASIK.…”
mentioning
confidence: 99%